Myocardial stretch-induced compliance is abrogated under ischemic conditions and restored by cGMP/PKG-related pathways - Leite-Moreira, André M.; Almeida-Coelho, João; Neves, João S.; Castro-Ferreira, Ricardo; Ladeiras-Lopes, Ricardo; Leite-Moreira, Adelino F.; Lourenço, André P. (Frontiers in Physiology, 2023)
Management of acute myocardial infarction (MI) mandates careful optimization of volemia, which can be challenging due to the inherent risk of congestion. Increased myocardial compliance in response to stretching, stretch-induced compliance (SIC) has been recently characterized and partly ascribed to cGMP/cGMP-dependent Protein Kinase (PKG)-related pathways. We hypothesized that SIC would be impaired in MI but restored by activation of PKG, thereby enabling a better response to volume loading in MI. We conducted experiments in ex vivo rabbit right ventricular papillary muscles under ischemic and non-ischemic conditions as well as pressurevolume hemodynamic evaluations in experimental in vivo MI induced by left anterior descending artery ligation in rats. Acutely stretching muscles ex vivo yielded increased compliance over the next 15 minutes, but not under ischemic conditions. PKG agonists, but not PKC agonists, were able to partially restore SIC in ischemic muscles. A similar effect was observed with phosphodiesterase-5 inhibitor (PDE5i) sildenafil, that was amplified by joint B-type natriuretic peptide or nitric oxide donor administration. In vivo translation revealed that volume loading after MI only raised cardiac output in rats infused with PDE5i. Contrarily to vehicle, sildenafil-treated rats showed a clear increase in myocardial compliance upon volume loading. Our results suggest that ischemia impairs the adaptive myocardial response to acute stretching and that this may be partly prevented by pharmacological manipulation of the cGMP/PKG pathway, namely with PDE5i. Further studies are warranted to further elucidate the potential of this intervention in the clinical setting of acute myocardial ischemia.